2021
DOI: 10.1590/0004-282x-anp-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy in COVID-19 is due to immune-mechanisms, pre-existing risk factors, anti-viral drugs, or bedding in the Intensive Care Unit

Abstract: Background: This mini-review aims to summarize and discuss previous and recent advances in the clinical presentation, pathophysiology, diagnosis, treatment, and outcome of SARS-CoV-2-associated peripheral neuropathies. Methods: Literature review. Results: Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 261 patients were retrieved. Peripheral neuropathy in patients with COVID-19 is frequent and predominantly due to immune mechanisms or neurotoxic side effects of drugs used to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 26 publications
(41 reference statements)
1
51
0
8
Order By: Relevance
“…Marzia Puccioni-Sohler [1], [2]  , André Rodrigues Poton [1]  , Milena Franklin [1]  , Samya Jezine da Silva [2]  , Rodrigo Brindeiro [3]  and Amilcar Tanuri [3] …”
Section: Current Evidence Of Neurological Features Diagnosis and Neur...mentioning
confidence: 99%
“…Marzia Puccioni-Sohler [1], [2]  , André Rodrigues Poton [1]  , Milena Franklin [1]  , Samya Jezine da Silva [2]  , Rodrigo Brindeiro [3]  and Amilcar Tanuri [3] …”
Section: Current Evidence Of Neurological Features Diagnosis and Neur...mentioning
confidence: 99%
“…Several studies have identified a number of neuropathologies associated with SARS-CoV-2, including pain-related conditions ( McFarland et al, 2021 ) but recent evidence suggests that SARS-CoV-2 does not cause viral neuropathy ( Finsterer et al, 2021 ). At present, there is evidence that neural damage during COVID-19 is associated with secondary immune mechanisms ( Finsterer et al, 2021 ). It is hypothesized that the systemic hyperinflammation seen in severe COVID-19 has the potential to contribute to nociceptor sensitization.…”
Section: Kynurenines In Peripheral Neuropathy During Covid-19mentioning
confidence: 99%
“…However, since both central and peripheral nervous system dysfunctions may be present, etiologies supported by inflammatory or autoimmune studies are also considered [ 6 ]. It was also suggested that peripheral neuropathies might result from neurotoxic side effects of drugs applied to treat COVID-19, e.g., Daptomycin, Linezolid, and Lopinavir [ 9 ].…”
Section: Introductionmentioning
confidence: 99%